The Implementation of Directed Reading Thinking Activity (DRTA) to Improve Students’ Reading Comprehension - Nurmadina HS; Yuliah Yuliah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
The goal of this research is to look into the use of Directed Reading Thinking Activity to improve students' reading comprehension in the tenth grade at SMAN 1 Tanete Riaja. The following research questions were addressed in this study: 1) How does the implementation of Directed Reading Thinking Activity (henceforth DRTA) improve students' reading comprehension?2) What are the students' perceptions toward the DRTA strategy's implementation? This study employs a quasi-experimental design with both an experimental and a control group. The experimental class was taught using the DRTA strategy, while the control class was taught using the conventional strategy. The participants in this study were chosen at random and were divided into two classes: class X-1, which consisted of 32 students as the experimental class, and class X-2, which consisted of 30 students as the control class. The data was gathered through a reading comprehension test and a questionnaire. According to the findings of this study, using the DRTA method increases students' scores more than using the conventional strategy. The experimental class has a mean score of 76.40, while the control class has a score of 50.3. It indicates that the DRTA strategy significantly improves students' reading comprehension and makes a positive contribution to their cognitive development. Furthermore, the results of the questionnaire show that the majority of students respond positively to the implementation of the DRTA strategy in the classroom.